2015
DOI: 10.4236/jdm.2015.54034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BMI and Lipids Profile in Type 2 Diabetic Subjects with Low and Raised Levels of Thyroid Hormone in Calabar, Nigeria

Abstract: Relationship between lipid levels and BMI was investigated in euthyroid, hyperthyroid, hypothyroid, general Type 2 diabetics, and non-diabetic control subjects. FT 4 , T 4 , T 3 and TSH did not differ in obese and non-obese diabetics but were higher in diabetics than in non-diabetics (p = 0.015, 0.012, 0.0164 respectively). Levels of FT 4 correlated with TC,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…Obesity correlated positively with HDL and LDL while it had negative correlation with total cholesterol and triglyceride. This was in line with a finding which showed that BMI correlated positively with TC and LDL-C in Type 2diabetics [29]. Type 2 diabetes mellitus is characterized by dyslipidemia the level of which is associated with BMI [29].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Obesity correlated positively with HDL and LDL while it had negative correlation with total cholesterol and triglyceride. This was in line with a finding which showed that BMI correlated positively with TC and LDL-C in Type 2diabetics [29]. Type 2 diabetes mellitus is characterized by dyslipidemia the level of which is associated with BMI [29].…”
Section: Discussionsupporting
confidence: 77%
“…This was in line with a finding which showed that BMI correlated positively with TC and LDL-C in Type 2diabetics [29]. Type 2 diabetes mellitus is characterized by dyslipidemia the level of which is associated with BMI [29]. The study by [29] also showed that Cholesterol levels in turn correlate with BMI indicating that lipid levels are influenced by BMI.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Obesity correlated positively with HDL and LDL. This was in accordance with a finding which showed that BMI correlated positively with TC and LDL-C. [8] Type 2 diabetes mellitus is characterized by dyslipidemia the level of which is associated with BMI. [8] The study by Udiong et al(2015) also showed that cholesterol levels correlates with BMI which indicates that the lipid levels are influenced by BMI.…”
Section: Discussionsupporting
confidence: 92%